The Effect of Globalization on Performance of Manufacturing Firms in South-South, Nigeria - Subeno, Therresa O.; Addah, Grace A.; Omogbiya, Oghenenyerhovwo Shulammite (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2025)
Globalization is the growing economic interdependencies of countries worldwide which resulted from increasing volume and variety of cross-border transactions in goods and services and of international capital flows, as well as the rapid and widespread diffusion of technology and information. This has increased competition level among Organizations thereby forcing them to improve their delivering capacity. Thus, Globalization suggests that greater openness yields unambiguously better performance in terms of higher level of output and income. Some indigenous Manufacturing industries in developing nations like ours ’Nigeria’ are afraid of being exploited and oppressed by foreign investors as a result have held themselves back from keying into the trend of Globalization in the globe. The main objective of this work is to examine the effects of Globalization on the performance of manufacturing firms in South-South Nigeria.  The survey research method will be employed to carry out this research. The researchers will utilize both the primary and secondary sources of data. The population of the study will include all senior staff of all selected Industries. The stratified random sampling method will be employed in selecting the sample size. At the end of the study, the results are expected to prove or disapprove the following hypotheses that will be tested at 5% level of significance (α=0.05); (i)H0: There is no significant relationship between trade liberalization and creativity, (ii)H0: There is no significant relationship between technology and productivity, (iii)H0: Quality goods and services have no significant relationship with customer’s satisfaction. The study will conclude that globalization is a sword of double edge that promotes and demote economic activities of any developing nation, therefore government will have to reposition its policies in order to monitor the activities of agents of globalization as it affects manufacturing sector.